Development of Self-Based Competency Test Application Based On Microsoft Excel To Improve Self-Efficacy of High School Students - Ulfah, Shafiyah; Arisanti, Dewi (Universitas Negeri Medan, 2020)
This study aims to analyze the computer-based Independent Competency Test (ICT) program that was developed to improve students' self-efficacy in physics subjects and to analyze the computer-based Independent Competency Test (ICT) program that was developed effectively used in increasing student self-efficacy used by participants students and teachers. This research uses the Research and Development (R&D) method which includes stages: (i) Identification of Potential and Problems; (ii) Analysis of Needs and Data Collection; (iii) System Design; (iv) System Implementation; (v) System Validation; (vi) System Revision; (vii) System Testing; and (viii) Final Systems. The subjects of this study were MAN 1 Medan students. The instrument used was testing aspects of functionality, usability, and student self-efficacy questionnaires. Based on the results of expert validation on the functionality test, it is obtained a percentage of 100% with very good criteria and has met the aspects of functionality. The results of expert validation on the usability test obtained a percentage of 93.15% with very high criteria and have met the usability aspect. Furthermore, the percentage obtained from the student questionnaire / self-efficacy questionnaire was 81% with very high criteria.